Chaihu Shugan powder alleviates liver inflammation and hepatic steatosis in NAFLD mice: A network pharmacology study and in vivo experimental validation - Lei, Sisi; Zhao, Shuai; Huang, Xiaoyan; Feng, Yuchao; Li, Zhishang; Chen, Li; Huang, Peiying; Guan, Hansu; Zhang, Haobo; Wu, Qihua; Chen, Bojun (Frontiers in Pharmacology, 2022)
Background: Nonalcoholic fatty liver disease (NAFLD) is the most common metabolic disease and is intertwined with cardiovascular disorders and diabetes. Chaihu Shugan powder (CSP) is a traditional Chinese medicine with a significant therapeutic effect on metabolic diseases, such as NAFLD. However, its pharmacological mechanisms remain to be elucidated. Methods: The main compounds of CSP were measured using LC-MS/MS. A network pharmacology study was conducted on CSP. Its potential active ingredients were selected according to oral bioavailability, drug similarity indices, and phytochemical analysis. After obtaining the intersected genes between drug targets and disease-related targets, the component-disease-target network and protein‐protein interaction analysis were visualized in Cytoscape. GO and KEGG enrichment analyses were performed using the Metascape database. Six-week-old male C57BL/6 mice fed a high-fat high-fructose diet for 16 weeks plus chronic immobilization stress for two weeks, an in vivo model, were administered CSP or saline intragastrically. Liver histology, triglyceride and cholesterol levels, ELISA, and RT-PCR were used to assess hepatic inflammation and steatosis. Immunohistochemistry and western blotting were performed to assess protein levels. Results: A total of 130 potential target genes in CSP that act on NAFLD were identified through network pharmacology assays, including tumor necrosis factor (TNF), interleukin-6 (IL6), interleukin-1β (IL-1β), and peroxisome proliferator-activated receptor γ (PPARG). KEGG enrichment analysis showed that the main pathways were involved in inflammatory pathways, such as the TNF and NF-κB signaling pathways, and metabolism-related pathways, such as the MAPK, HIF-1, FoxO, and AMPK signaling pathways. The results in vivo showed that CSP ameliorated liver inflammation and inhibited hepatic fatty acid synthesis in the hepatocyte steatosis model. More specifically, CSP therapy significantly inhibited the expression of tumor necrosis factor α (TNFα), accompanied by a decrease in TNF receptor 1 (TNFR1) and the ligand availability of TNFR1. Conclusion: Through the combination of network pharmacology and in vivo validation, this study elucidated the therapeutic effect of CSP on NAFLD, decreasing liver inflammation and inhibiting hepatic fatty acid synthesis. More specifically, the anti-inflammatory action of CSP was at least partially mediated by inhibiting the TNFα/TNFR1 signaling pathway.